Bortezomib-resistant multiple myeloma patient-derived xenograft is sensitive to anti-CD47 therapy. (November 2022) - Yue, Yanhua; Cao, Yang; Wang, Fei; Zhang, Naidong; Qi, Ziwei; Mao, Xunyuan; Guo, Shuxin; Li, Feng; Guo, Yanting; Lin, Yan; Dong, Weimin; Huang, Yuhui; et al.
Abstract: Multiple myeloma (MM) remains an incurable hematologic malignancy due to its frequent drug resistance and relapse. Cluster of Differentiation 47 (CD47) is reported to be highly expressed on MM cells, suggesting that the blockade of CD47 signaling pathway could be a potential therapeutic candidate for MM. In this study, we developed a bortezomib-resistant myeloma patient-derived xenograft (PDX) from an extramedullary pleural effusion myeloma patient sample. Notably, anti-CD47 antibody treatments significantly inhibited tumor growth not only in MM cell line-derived models, including MM.1S and NCI-H929, but also in the bortezomib-resistant MM PDX model. Flow cytometric data showed that anti-CD47 therapy promoted the polarization of tumor-associated macrophages from an M2- to an M1-like phenotype. In addition, anti-CD47 therapy decreased the expression of pro-angiogenic factors, increased the expression of anti-angiogenic factors, and improved tumor vascular function, suggesting that anti-CD47 therapy induces tumor vascular normalization. Taken together, these data show that anti-CD47 antibody therapy reconditions the tumor immune microenvironment and inhibits the tumor growth of bortezomib-resistant myeloma PDX. Our findings suggest that CD47 is a potential new target to treat bortezomib-resistant MM. Graphical Abstract: ga1 Highlights: Anti-CD47 therapy inhibits the growth of bortezomib-resistant MM. Anti-CD47 therapy polarizes tumor-associated macrophages from M2 to M1 phenotype in MM. Anti-CD47 therapy normalizes tumor vascular function in MM.